Evolution and human motivation: A fundamental motives framework. Issue 6 (June 2017) - Schaller, Mark; Kenrick, Douglas T.; Neel, Rebecca; Neuberg, Steven L.
Abstract: An evolutionary perspective on human motivation provides a means of identifying conceptually distinct motivational systems (including motives pertaining to self‐protection, disease avoidance, affiliation, status, mate acquisition, mate retention, and parental care), each of which has unique implications for affect, cognition, and behavior. We provide an illustrative summary of some of these empirically documented implications—including those pertaining to individual differences in chronic motivational tendencies, as well as additional implications that follow from temporary activation of these motivational systems. We also summarize a variety of broader implications—both conceptual and practical—that follow from this framework.